Correlation between class 1 integron of Escherichia coli and multidrug resistance in lower respiratory tract infection: Class 1 integron of E. coli and multi resistance - Wang, Yu; Kong, Bingbing; Yang, Wenping; Zhao, Xin (The Journal of Infection in Developing Countries, 2017)
Introduction: Class 1 integrons are mobile genetic elements considered to be responsible for the transfer of multidrug resistance. This study aimed to investigate the distribution of type 1 integrons in multidrug-resistantEscherichiacolifrom hospital-acquired lower respiratory tract infections. Methodology: Clinical strains of E. coli were isolated from patients with hospital-acquired lower respiratory tract infections in the emergency intensive care unit from January to December 2014. Drug sensitivity testing was performed using the Kirby-Bauer method. The combination disk method was used to detect extended-spectrum β-lactamase (ESBL), and polymerase chain reaction (PCR) amplification was used to detect the intI1 gene. Results: Among 58 E. coli strains, resistance to β-lactam antibiotics ranked as follows: imipenem (0.0%), cefoperazone/sulbactam sodium (25.9%), ceftazidime (37.9%), and cefepime (39.7%); other β-lactam antibiotic resistance rates were all > 50%. The resistance rates to amikacin, ciprofloxacin, gentamicin, and cotrimoxazole were32.8%, 63.8%, 70.7%, and 81.0%, respectively. In total, 31 (53.4%) isolates were positive for class 1 integron and carried 4 different sizes of amplification fragments: 800, 1,600, 1,900, and 2,600 bp. Among 43 ESBL-positive isolates, 27 (62.8%) also carried class 1 integron; among 15 ESBL-negative isolates, 4 carried class 1 integron (26.7%). The positive rate for class 1 integron in ESBL-producing strains was significantly higher than that in non-ESBL-producing strains. The rates of resistance of integron-positive isolates to ceftriaxone, cefotaxime, amikacin, ciprofloxacin, and cotrimoxazole were significantly higher than those in integron-negative isolates. Conclusions: Class 1 integrons are widely distributed in E. coli and are associated with multidrug resistance.